Peningkatan Kompetensi Alat Ukur Siswa Teknik Kendaraan Ringan Kelas XII SMK Ki Hajar Dewantara Brebes - Sigit Setijo Budi; Syarifudin; Faqih Fatkhurrozak; Firman Lukman Sanjaya; Andre Budhi Hendrawan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The basic competencies of SMK graduates are demanded to be adaptive according to the needs of the business world and the industrial world. Basic competence is the basis for the depth of graduate competence. Community service aims to improve the basic competence of technical measurement tools for Class XII Students of the Light Vehicle Engineering Department, Ki Hajar Dewantara Vocational School, Brebes Regency. The method used was a workshop that was held on June 5 and 6 2024. The tool used to measure the success of the community service program was the implementation of evaluation at the pre-workshop and post-workshop stages. The results of the activity explained that the pre test was carried out to find out the initial condition of the participants' competence by 15%. Meanwhile, the final competency of the participants, which was carried out through post-workshop evaluation, increased by 66.67%. The provision of Refreshing material and PjBL practicum measuring tools is the key to the success of the workshop.